(untitled) (Eastern Medical College Journal, 2025)
Background: Acute lower respiratory illness (ALRI) contributes to significant mortality in developing countries and the majority of this is secondary to hypoxemia. Early detection of hypoxemia and treatment improves the outcome in these children. The aim of the study is to detection of hypoxaemia by analysis of arterial blood gas in children with ALRI admitted to Paediatrics ward of Chattogram Medical College Hospital (CMCH), Chattogram, Bangladesh. Materials and methods: Ethical permission was taken from the Institutional Review Board of Chittagong Medical College (CMC) for this study. In this hospital based cross sectional study a total of 100 patients with ALRI aged between 2 to 60 months in paediatrics ward of CMCH were included. Besides demographic factors (age, sex, place of residence) and presenting symptoms were recorded. Oxygen saturation of these children was recorded by ABG analysis to detect hypoxaemia. Children having PaO2<60 mmHg are considered hypoxaemic. Continuous variables were reported as the mean±SD and categorical variables were reported as frequency (percentages). Frequency of different symptoms and signs in both groups was calculated and analysis by ꭓ2 tests. Statistical significance was defined as p<0.05 and confidence interval was set at 95%. Results: Among the 100 children, 46% had hypoxaemia as per ABG criteria (pO2 <60 mmHg). In this study we found that age 2-12 months 41 (89.1%), female children 21 (45.7%) and residence of rural area 32 (69.65) were more hypoxemic. Among hypoxaemic patients’ pH ranges from 7.04-7.50, pO2 ranges from 9-58 mmHg and pCO2 ranges from 18.30-60.40 mmHg. Among ALRI patients the majority were diagnosed with bronchopneumonia (50%) followed by bronchiolitis (41%), bronchial asthma (5%) and kerosene poisoning (4%). Conclusion: Hypoxaemia is a very common and treatable complication of childhood respiratory infections in developing countries. It is a life-threatening condition that requires early detection and prompt treatment. Eastern Med Coll J. July 2025; 10 (1): 1-5